Art world of children's poetic creativity Igor Sichovik (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
The article is devoted to the diversity of poetic creativity of contemporary Ukrainian children's writer Igor Sichovik. The article presents brief information about the life and creative way of children's writer Igor Sichovik. The material of the research is the poetic writings of the writer, such as verses, riddles, scrambling, which are analyzed in the context of literature for children, and the synthesis of folklore and literary genres is considered, and the poetic depiction of images of real reality and the environment is interpreted. The specificity of such analysis makes it possible to follow the artistic world of childhood. The study of works is carried out from the standpoint of communicative, cognitive, and educational approaches.
Keywords: poetry; poetic creativity; artistic world; poetic image; mood; worldview; children's imagination and fantasy; Igor Sichovik; contemporary literature for children; children's writer; short stories; riddles; poems; child's inner world; cognitive aspect of poetry